Best Answer

It is a straight line with gradient -A/B and intercept C/B.

User Avatar

Wiki User

12y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What can you say about the graph Ax plus By equals C about the graph Ax plus By equals C?
Write your answer...
Still have questions?
magnify glass
Related questions

What can you say about the graph of Ax plus By equals C if B is equal to zero?

If B=0, then the graph does not depend on the value of y. This is a vertical line at x = C/A

How can you describe the graph of the equation ax plus by equals c?

ax + by = cThe graph if that equation is a straight line whose slope is (-a/b)and whose y-intercept is (c/b).

What is an equation that can be written in the from Ax plus By equals C whose graph is a straight line?

A linear equation ?

What is Ax plus By equals C with a qraph that is a straight line?

[ Ax + By = C ] If 'A', 'B', and 'C' are numbers, then the graph is always a straight line, and the equation is a "linear" one.

How are the graphs of functions defined by rules like y equals ax plus bx different from those of functions with rules like y equals ax plus c?

The graph of the first form passes through the origin while the second does not - unless c = 0.

Ax plus b equals bx plus c then x equals?

Ax + B = Bx + C Ax - Bx = (C - B) x (A - B) = (C - B) x = (C - B) / (A - B)

What is the compound sentence of abs value ax plus b equals 15?

ax + b = 15 or ax + b = -15

Write the equation of the line in the form Ax plus By equals C?

y = (c - Ax) / (B)

If x2 - 13x plus 42 equals x plus Ax plus B then A plus B equals?

2x - 13x + 42 = x +ax + b a + b = 2(x - 6.5x + 21) = 34 = a + b

What is the y intercept of the graph of -5x plus 10y equals 20?

Solve the equation for y. This will give you an equation similar to y = ax + b, where a is the slope, and b is the y-intercept.

What kind of equation is y equals ax plus b?

a function

When Ax plus By equals C passes through the origin will C equal 0 on the graph?

Yes Ax + By = C As the line passes through the origin then x = 0 when y = 0. Substituting gives, 0 + 0 = C therefore C = 0.